Analisis Korelasi Frekuensi Konsumsi Kopi terhadap Tekanan Darah Sistolik dan Diastolik pada Orang Dewasa - Hadi Nur Efendi; Ayik Nikmatul Laili; Mohammat Fairosi (Lembaga Pengembangan Kinerja Dosen, 2025)
Coffee is one of the most widely consumed beverages worldwide, including in Indonesia. Coffee consumption has become part of people's daily habits, whether as a companion for work, relaxation, or as part of social culture. However, this habit is often associated with the potential for increased blood pressure due to caffeine, which is a stimulant to the central nervous system and can affect the function of the heart and blood vessels. This study aims to analyze the relationship between the frequency of coffee consumption and systolic and diastolic blood pressure in adults. The research method used a quantitative approach with a correlational design. The study sample consisted of 100 adult respondents selected through a purposive sampling technique based on certain criteria, such as not currently taking antihypertensive medication and having no history of serious cardiovascular disease. Data collection was carried out in two stages. First, respondents completed a questionnaire containing information on the frequency and habits of coffee consumption, including the number of cups per day and the type of coffee consumed. Second, blood pressure was measured using a digital sphygmomanometer to obtain accurate systolic and diastolic blood pressure data. The results of the statistical analysis showed a significant positive correlation between the frequency of coffee consumption and increases in blood pressure, both systolic and diastolic. Specifically, respondents who consumed more than two cups of coffee per day tended to have higher blood pressure values compared to those who consumed one cup or less. This finding has important implications for health promotion efforts, particularly in educating the public about wise coffee consumption. Recommendations include limiting coffee intake, choosing coffee with low caffeine content, and balancing this with a healthy diet, regular physical activity, and stress management as part of a healthy lifestyle.